Konstruksi Realitas Media Massa Detik.Com Tentang Pemberitaan Kasus Kejahatan Seksual Tahun 2022 - Azalia Indra Pinastika; Agus Triyono (Institut Nalanda, 2024)
This research was conducted using Robert Entman's framing model analysis on the online media detik.com. This research discusses sexual crimes in 2022 committed by the defendant JE as an employee of the Indonesian Morning School in Batu City, in which the defendant invited children or students to have sexual intercourse. This research uses a qualitative approach. The object of this research is the Indonesian Morning School in Batu City. This SPI case went very viral in 2022, the defendant was sentenced to 15 years in prison or a fine of 300 million rupiah at the District Court, the defendant took a well-known lawyer named Hotma Sitompul. The results of the research focus more on the meaning and prominence of messages in several news frames on detik.com.